Factors Affecting Student Satisfaction With The Quality of Training Services of The University of Economics, Vietnam National University, Hanoi (VNU) (International Journal of Scientific Research and Management (IJSRM), 2023)
This article studies the factors affecting the level of student satisfaction with the quality of training services at the University of Economics, VNU. The authors used the survey method through questionnaires, collected primary data and included it in a multivariate regression model for analysis and evaluation. Research results show that there are five factors that affect student satisfaction including: Lecturers, facilities, training programs, non-academic factors, and reputation. Among these factors, reputation is the factor that has the strongest impact on student satisfaction, followed by the group of lecturer factors, non-academic factors and training programs, and the remaining impact is facilities. at least. The authors propose a number of solutions to improve the quality of university training.